Hubungan Kadar Gula Darah Puasa dan Profil Lipid Pada Penderita Diabetes Melitus Tipe 2 dengan Kejadian Stroke Iskemik di RSUD R.A Basoeni Mojokerto - Rahayu, Putri Nur (Jurnal Biosains Pascasarjana, 2020)
ABSTRACT Diabetes Mellitus is one of the most popular degenerative disease in the medical worlds. Every years, the incidence rate of this disease always shows an increase. In 2010 reported that 1,9 million of 35 years old or more diabetics also suffering the stroke complications. In addition there is an increase of 1.2% every month in people with diabetes mellitus with the incidence of ischemic stroke, so there is a need for preventive action by recognizing risk factors that can be changed. The purpose of this research is to determine the relations between fasting blood sugar levels and lipid profiles in patients with type 2 diabetes mellitus and ischemic stroke in RSUD R.A Basoeni Mojokerto from January to March 2020. This research using observational method. Research involving 34 sample of 40 years old and above patients with type 2 diabetes mellitus and ischemic stroke. Thereseach of the relations between fasting blood sugar levels and lipid profiles from the total respondents (34 patients) shows as follows, The average of the cholesterol total level is 189 mg/dl, and 35% from them (12 respondents) have >200 mg/dl of the cholesterol total level. The average of the cholesterol HDL level is 36 mg/dl, and 65% from them (22 respondents) have <40 mg/dl of the HDL cholesterol level. The average of the LDL cholesterol level is 112 mg/dl, and 24% from them (8 respondents) have >150 mg/dl of the LDL cholesterol level. The average of the triglyceride level is 211 mg/dl, and 47% from them (16 respondents) have >200 mg/dl of the triglyceride level. This shows that there is no correlation between fasting blood sugar level with the cholesterol total level, the cholesterol HDL level, and cholesterol LDL level. However, there is a correlation between fasting blood sugar level and triglyceride level. Keyword : Type 2 Diabetes Mellitus, Ischemic Stroke (CVA Infark), Fasting Blood Sugar, Lipid Profile ABSTRAK Diabetes melitus merupakan salah satu penyakit degeneratif yang paling popular dalam dunia kedokteran. Tingkat insidensi dari tahun ketahun menunjukan peningkatan. Pada tahun 2010 jumlah penderita diabetes melitus yang berusia 35 tahun atau lebih dilaporkan 1,9 juta mengalami komplikasi stroke Selain itu terdapat kenaikan 1,2% setiap bulannya pada penderita diabetes melitus dengan kejadian stroke iskemik sehingga perlu adanya tindakan preventif dengan mengenal faktor-faktor risiko yang dapat diubah. Tujuan penelitian ini untuk mengetahui hubungan antara kadar gula darah puasa dan profil lipid pada penderita diabetes melitus tipe 2 dengan kejadian stroke iskemik di RSUD R.A Basoeni Mojokerto pada bulan Januari sampai Maret 2020. Penelitian ini menggunakan metode observasional. Pada penelitian ini diperoleh 34 sampel penderita diabetes melitus tipe 2 dengan kejadian stroke iskemik yang merupakan pasien awal dengan kriteria usia diatas 40 tahun dan penderita stroke iskemik yang telah dinyatakan positif stroke.Hasil pemeriksaan terhadap hubungan kadar gula darah puasa dengan profil lipid menunjukan rerata kadar total kolesterol sebesar 189 mg/dl dengan kadar kolesterol >200 mg/dl sebanyak 12 responden (35%). Rerata kadar HDL kolesterol sebesar 36 mg/dl, dengan kadar kolesterol HDL <40 mg/dl sebanyak 22 responden (65%). Rerata kadar LDL kolesterol sebesar 112 mg/dl dengan kadar kolesterol LDL >150 mg/dl sebanyak 8 responden (24%). Rerata kadar trigliserida sebesar 211 mg/dl dengan kadar trigliserida >200 mg/dl sebanyak 16 responden (47%). Hal ini menunjukan bahwa tidak ada korelasi antara kadar gula darah puasa dengan kadar total kolesterol, HDL kolesterol, LDL kolesterol dan ada korelasi atau hubungan antara kadar gula darah puasa dengan kadar trigliserida. Kata kunci : Diabetes Melitus tipe 2, Stroke Iskemik (CVA Infark), Gula Darah Puasa, Profil Lipid